The Effectiveness of Assertive Training in Enhancing Self-Confidence Through Sundrang Learning in Bugis Elementary Schools - Usman Usman; Ma’ruf Ma’ruf; Putriana Putriana; Moh. Wardi Moh. Wardi; Moh Zainol Kamal; Hodairiyah Hodairiyah (AL-ISHLAH: Jurnal Pendidikan, 2026)
Self-confidence is a critical determinant of elementary students’ learning success, particularly within culture-based contexts such as Sundrang in Bugis communities. However, many students exhibit low confidence in expressing opinions, participating in discussions, and engaging in classroom interactions. Although assertive training is known to enhance communication and confidence, its integration into local cultural learning remains underexplored.This study employed a quantitative quasi-experimental pretest–posttest control group design. Sixty fifth-grade students from Bugis elementary schools were assigned to an experimental group (n = 30) and a control group (n = 30). The experimental group received assertive training integrated into Sundrang learning, while the control group followed conventional instruction. Data were collected using a validated and reliable Likert-scale self-confidence questionnaire and analyzed through normality, homogeneity, and independent-samples t-tests.The findings revealed a statistically significant improvement in self-confidence among students in the experimental group compared to the control group. Students exposed to assertive training demonstrated greater gains in public speaking, social interaction, and the ability to express opinions during Sundrang learning activities.The results indicate that integrating assertive training into culture-based learning effectively enhances students’ self-confidence. This approach supports not only communication skills but also active participation in culturally relevant educational settings. Accordingly, incorporating assertive training into elementary curricula, particularly in local cultural learning contexts, is recommended to foster students’ social competence and overall confidence.